Clinical features and prognostic factors analysis of intravenous leiomyomatosis - Chen, Jingying; Bu, Hualei; Zhang, Zhaoyang; Chu, Ran; Qi, Gonghua; Zhao, Chen; Wang, Qiuman; Ma, Xinyue; Wu, Huan; Dou, Zhiyuan; Wang, Xia; Kong, Beihua (Frontiers in Surgery, 2023)
Background: The treatment and prognostic factors of intravenous leiomyomatosis (IVL) remain lacking systematic evidence. Methods: A retrospective study was conducted on IVL patients from the Qilu Hospital of Shandong University, and IVL cases were published in PubMed, MEDLINE, Embase and Cochrane Library databases. Descriptive statistics were used for the basic characteristics of patients. The Cox proportional hazards regression analysis was used to assess the high-risk factors related to the progression-free survival (PFS). The comparison of survival curves was performed by Kaplan–Meier analysis. Results: A total of 361 IVL patients were included in this study, 38 patients from Qilu Hospital of Shandong University, and 323 patients from the published literature. Age ≤45 years was observed in 173 (47.9%) patients. According to the clinical staging criteria, stage I/II was observed in 125 (34.6%) patients, and stage III/IV was observed in 221 (61.2%) patients. Dyspnea, orthopnea, and cough were observed in 108 (29.9%) patients. Completed tumor resection was observed in 216 (59.8%) patients, and uncompleted tumor resection was observed in 58 (16.1%) patients. Median follow-up period was 12 months (range 0–194 months), and 68 (18.8%) recurrences or deaths were identified. The adjusted multivariable Cox proportional hazard analysis showed age ≤45 years (vs. >45) (hazard ratio [HR]=2.09, 95% confidence interval [CI] 1.15-3.80, p=0.016), and uncompleted tumor resection (vs. completed tumor resection) (HR=22.03, 95% CI 8.31-58.36, p<0.001) were high-risk factors related to the PFS. Conclusion: Patients with IVL have a high probability of recurrence after surgery and a poor prognosis. Patients younger than 45 years and with uncompleted tumor resection are at higher risk of postoperative recurrence or death.